Determining friction coefficients for round balls by using center -of-pressure - Alaways, L.; Krumenacker, N. (Procedia Engineering, 2012)
The non-destruction determination of static coefficient-of-friction for round balls can be challenging. The traditional tilt-table test on an individual ball will just cause the ball to roll off the table and little is accomplished. A three-ball test can be conducted however the balls will tumble if the friction is too high. An additional problem occurs with this type of testing in that the precise moment of impending slip is determined by observing the ball or ball sample material and this moment is hard to detect. A new nondestructive method of determining the precise moment of impending slip for a single-ball is presented using the center-of-pressure and a detectable change in the normal force acting on the ball.